Capacitively Coupled Converter (C3) for HighPower DC-DC Conversion - Ehsani, Mehrdad; Bilgiç, Mehmet Oruç; Khan, S. (My University, 1991)
The capacitive coupled converter for high-power voltage source DC-DC applications is described. Its steady-state and dynamic behavior are analyzed theoretically and by computer simulation. Factors affecting its operation and control are discussed and some design rules are presented. A proof-of-principle model of the capacitive coupled converter was constructed, and its waveforms were recorded
Keywords: Converter; Power